Human cytomegalovirus-IE2 suppresses antigen presentation of macrophage through the IL10/STAT3 signalling pathway in transgenic mouse - Xianjuan Zhang; Qing Wang; Shuo Han; Guanghui Song; Bin Wang; Yunyang Wang (PLoS ONE, 2025)
Human cytomegalovirus (HCMV) has evolved sophisticated strategies to evade host immune defenses, enabling its persistent survival in human populations. HCMV intermediate-early protein 2 (IE2) has been identified as a crucial factor in immune evasion mechanisms. However, the specific immunomodulatory effects of IE2 on antigen presentation remain insufficiently explored. In this study, we established a transgenic mouse model to systematically examine the impact and molecular mechanisms of IE2 on macrophages (Mφs) antigen presentation in vivo. Our findings demonstrated that IE2 modifies Mφs’ function by preventing their phagocytic activity and polarization. Additionally, IE2 inhibits Mφs overactivation both in vivo and in vitro, which raises IL-10 levels and activates the downstream mediator STAT3, which in turn decreases T cell immune responses by encouraging T helper 2 (Th2) type responses. In conclusion, these findings underscore the potential of IE2 as a critical regulator of immune evasion and may contribute to the development of novel, targeted therapeutic strategies against the virus.